Anti-asthmatic and airway smooth muscle relaxation effects of polysaccharides from lignosus rhinocerotis in animal models ROM Lignosus rhinocerotis IN ANIMAL MODELS - Daku, Abubakar Bishir (2025)
Asthma is a chronic airway disease which is associated with several characteristics including bronchoconstriction, airway vasodilation, oedema, sensory nerve activation, and hypersensitivity. Systemic corticosteroids are crucial for managing moderate-to-severe asthma but are associated with various adverse effects with long-term use. This has driven researchers to explore safer complementary and alternative anti-asthmatic interventions to mitigate these exaggerated immune responses. Mushroom polysaccharides (MP) have been reported to contain β-glucan compounds and polysaccharide-protein complexes, which are known to exhibit several bioactivities, including anti-inflammatory, immunomodulatory, antitumor, and antioxidant properties, as demonstrated in numerous in vivo and in vitro studies. However, the potential of inhaled Lignosus rhinocerotis polysaccharide (LRP) to ameliorate asthma pathophysiology remains undetermined, and current research on its bioactive properties is limited. Therefore, this study aimed to (i) isolate and determine the polysaccharide composition of LR mushrooms, (ii) determine LRP inhalation delivery, (iii) establish a BALB/c mouse model of OVA-challenged allergic asthma and determine the effect of LRP on asthma pathophysiology, and (iv) determine the effect of LRP on airway receptor contractility in guinea pig tracheal (GPT) rings. The LRP DEAE-cellulose and Sephadex G-100 column elution exhibited a single symmetrical peak fractionated polysaccharide fraction. The megazyme β-glucan assay revealed that the percentages of α- and β-glucans in LRP were 21.52% (±0.53) and 21.07% ± (2.19), respectively. HPLC analysis revealed that LRP was a typical heteropolysaccharide composed of mannose, ribose, rhamnose, glucose, galactose, xylose, and arabinose. LRP spray drying was shown to produce unstable LRP powders due to its volatility and hygroscopic nature. Nebulization of the LRP solution-produced inhalable aerosols for lung delivery, the in vitro aerosol deposition using NGI demonstrated fine particle fraction (FPF) of 62.84, mean median aerodynamic distribution (MMAD) of 4.16, and geometric standard deviation (GSD) of 1.83. LRP nebulization treatment (4, 8, and 40 mg/ml) in an OVA-challenged mouse model of asthma significantly inhibited airway inflammation, and Cox-2, iNOS, and ADAM33 lung inflammatory gene expression (p<0.05), with 8 and 40 mg/ml treatment groups expressing the most significant effect. Furthermore, LRP demonstrated an airway relaxation effect independent of beta receptors, potentially through muscarinic and histamine receptor antagonism in carbachol-and histamine-pre-contracted GPT rings (p<0.05). These findings suggest the therapeutic potential of LR mushroom polysaccharides as complementary alternatives for the management of allergic asthma